Analysis of perceptions of managers and local communities in the application of principles in Ranca Upas tourism park - Febriansyah, Muhammad; Rahmafitria, Fitri (Community Service for Sustainable Community Journal, 2024)
Background: Ecotourism that involves local communities emphasizes active participation from local residents. This concept is based on the understanding that local populations possess indigenous knowledge about the natural environment and cultural heritage, which can serve as a tourism attraction. Therefore, community involvement is a crucial aspect of ecotourism development. This study focuses on the ecotourism management of Wana Wisata Ranca Upas and how it integrates local communities. Methods: A qualitative paradigm was applied as the research framework, following a post-positivist philosophy to explore phenomena in a natural setting. Data collection was conducted through triangulation, with an inductive approach to analysis. The study prioritized a deep understanding of community involvement over generalization. Findings: The analysis showed that the management of Wana Wisata Ranca Upas is committed not only to commercial aspects but also to environmental sustainability, community education, and providing significant economic and social benefits to local communities. Community motivation for participating in ecotourism varied, with many viewing it as a source of substantial income. However, there is a gap in ecotourism-related knowledge between the management, which operates according to Perhutani’s vision and mission, and the local communities, who often do not fully understand ecotourism principles. Factors influencing these differences in perception include access to information, background, interests, decision-making processes, and trust. Conclusion: The study concludes that while Wana Wisata Ranca Upas emphasizes sustainability and ecotourism principles, there remains a knowledge gap between management and local communities. Bridging this gap is essential for the long-term success of ecotourism in the area.  Novelty/Originality of this study: This study highlights the disconnect between management's vision and the local community's understanding of ecotourism, emphasizing the need for improved communication and education to foster more effective and sustainable community participation in ecotourism development.